Bio-climatic house a sustainable house for Philippine setting - Carlos-Manuel, Jane Anne (College of Architecture, University of the Philippines, Diliman, 2002)
To design a bio-climatic house that will respond to the living environment, ecology of the place, conserve resources and promote economy and attain sustainability. It shall include integration of bio-climatic design with zero-waste technology, and eng resource conservation that will help preserve the natural ecology, lessen adverse effect to the living environment and promote green architecture essential for sustainability.